Perceptions and Beliefs of Urban Poor Women on Reproductive Health: A Case Study - Rolda, Realidad S. (Philippine Social Sciences Review; Social Sciences and Health Issue, Ed. Carmen C. Jimenez, 2010)
This is an ethnographic study of the urban poor women of Bagbag, Novaliches, regarding their perceptions and beliefs on reproductive health. As such, it highlights the cultural beliefs, practices and rituals observed during pregnancy and childbirth. Lack of information about the importance of reproductive health explains in part why traditional beliefs are maintained and upheld as strategies and tactics used by women in safeguarding their well being. The findings show that the women of Bagbag, Novaliches have no reproductive rights, such being the prerogative of the husbands. Nonetheless, the men are supportive to and solicitous of their wives during pregnancy, assisting in household chores. They take over their wive’s responsibilities until their “recovery” from childbirth.